Vaccine delivery systems toward lymph nodes - Ding, Yingyue; Li, Zhaoting; Jaklenec, Ana; Hu, Quanyin (Advanced drug delivery reviews, 2021)
Vaccines play an important role in the control and prevention of human infectious diseases such as the ongoing COVID-19 pandemic. The successful vaccination needs to effectively deliver antigenic substances to induce a strong protective or therapeutic immune response. In this review, the lymph node structure, the administration routes and the most popular vaccine delivery systems together with their applications are carefully summarized with a special focus on the designing of the vaccine delivery strategies to overcome the barriers and strengthen the immune response against infectious diseases. [Display omitted] Strategies of improving vaccine targeting ability toward lymph nodes have been attracting considerable interest in recent years, though there are remaining delivery barriers based on the inherent properties of lymphatic systems and limited administration routes of vaccination. Recently, emerging vaccine delivery systems using various materials as carriers are widely developed to achieve efficient lymph node targeting and improve vaccine-triggered adaptive immune response. In this review, to further optimize the vaccine targeting ability for future research, the design principles of lymph node targeting vaccine delivery based on the anatomy of lymph nodes and vaccine administration routes are first summarized. Then different designs of lymph node targeting vaccine delivery systems, including vaccine delivery systems in clinical applications, are carefully surveyed. Also, the challenges and opportunities of current delivery systems for vaccines are concluded in the end.